Utilization of Anadara granosa as a Liming Materials for Swamp Fish Ponds for Pangasius sp Culture - Jubaedah, Dade; Marsi, Marsi; Rizki, Rani Ria (Aquacultura Indonesiana, 2017)
Availability of water in swamp areas is abandon almost throughout the year, therefore these areas are potential for aquaculture development. However, the characteristics of swamp water is mainly acid water, therefore, it becomes mayor problems in swamp fish culture development. Liming of ponds is intended to increase pH value of soil and water  of fish ponds. A. granosa shells is one of domestic waste containing of 61.16% CaO and 21.65% MgO, therefore it can be used as an alternative material for liming of fish ponds. The aims of this research was to evaluate the potency of lime derived from A. granosa shells to raise soil’s and water’s pH, and to evaluate its effect to survival and growth of Pangasius sp. The research was conducted and arranged based upon completely randomized design with five treatments and three replications. The treatments used consisted of different dosages of lime, namely : P1) 1 ton/ha; P2) 2 ton/ha; P3) 3 ton/ha; P4) 4 ton/ha and P5) 5 ton/ha of lime equivalent to CaO. The results showed that both the soil and water reach a neutral pH at a dosage of 2 ton/ha (P2), 3 ton/ha (P3), 4 ton/ha and 5 ton/ha. The dosage of 5 ton/ha (P5) was the best treatments among all treatments, with a highest survival rate (100%), absolute growth of fish lenght (9.35 cm) and weight (40.69 g), as well as feed efficiency (110.97%).